Significance of Testing Anti-Thyroid Autoantibodies in Patients with Deranged Thyroid Profile. (11th April 2018) - Tipu, Hamid Nawaz; Ahmed, Dawood; Bashir, Muhammad Mukarram; Asif, Naveed
Abstract : Background. We hypothesized that anti-thyroid antibodies are more often positive in individuals with deranged thyroid profile. Methods. This prospective cohort was done in Immunology Department, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from Jan 2017 to Oct 2017. All the samples that were referred to us for testing anti-thyroid antibodies (anti-TPO or anti-TG antibodies) and thyroid profile were included in the study. There were no exclusion criteria. Tests for anti-thyroid antibodies were performed by ELISA and thyroid profile by chemiluminescence. SPSS 23.0 was used for statistical analysis. Results. Over a course of a ten-month study period, we received a total of 316 serum samples for anti-TPO/TG antibodies along with thyroid profile testing (TSH). These included 115 males (36.4%) and 201 females (63.6%). Their age ranged from 3 to 89 years (mean ± SD, 42.22 ± 18.09). Anti-TPO antibodies were more often positive when TSH was deranged (p value 0.001). Anti-TPO antibodies are more often raised in females, in terms of both prevalence (p 0.001) and mean rank (p 0.002). Conclusion. As anti-thyroid antibodies are more often present when TSH is deranged, such individuals should be screened for anti-thyroid antibodies. This importance of screening is compounded by the fact that anti-thyroid antibodies may be positive in a significant percentage of elderly people.